2014
DOI: 10.1007/s00464-014-3973-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of early gastric cancer with lymphovascular invasion or positive vertical resection margin after endoscopic submucosal dissection

Abstract: Close surveillance may be suggested as an option for EGC patients for whom a surgical approach is difficult, who exhibit a positive vertical margin after ESD, and who have no lymphovascular or deep submucosa invasion after ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Although several studies have described the clinical outcomes of noncurative gastric ER patients, the definition of noncurative gastric ER differs between studies; most of these studies have assessed the clinical outcomes of noncurative gastric ER patients in small numbers of patients without detailed statistical analysis [15][16][17][18][19][20][21][22][23][24][25]. For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several studies have described the clinical outcomes of noncurative gastric ER patients, the definition of noncurative gastric ER differs between studies; most of these studies have assessed the clinical outcomes of noncurative gastric ER patients in small numbers of patients without detailed statistical analysis [15][16][17][18][19][20][21][22][23][24][25]. For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25]. To the best of our knowledge, the present study is the largest study demonstrating the clinical outcomes of more 500 noncurative gastric ESD patients, including long-term survival outcomes with a median follow-up period of more than 5 years and clinicopathological factors associated with metastasis and gastric-cancer-related death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…53 Interestingly, Noh et al suggested that close surveillance might be a feasible strategy for patients with EGC who present positive vertical margin without LVI or deep submucosa invasion, especially for whom surgery might be risky. 54 A scoring system, named as eCura, was established to categorize patients into three risk groups in order to address the risk of LNM in Japan. In its validation stage, noncurative ESD followed by additional surgery was recommended for patients in the high LNM risk group, whose 5-year cancer-specific survival appeared to be 90.1%.…”
Section: Number Of Studiesmentioning
confidence: 99%